Skinhead history, identity, and culture - Valeri, Robin Maria (Routledge studies in crime and society, 2018)
Preface -- Skinhead history -- Racist and non-racist skins : an analysis of why they, join, stay, and quit -- Gay skinheads: a part of or apart from the skinhead moment -- Female skinheads -- Skinhead music : the beat goes on -- Exploring skinhead identity through an analysis of skinhead websites -- Social networks, and social media -- Conclusion: who is a true skinhead? -- Index